Coping with cyberbullying victimization: an exploratory study of Chinese adolescents in Hong Kong - Chan, Heng Choon (International journal of law, crime and justice, 2017)
Limited information is available on how victims cope with their cybervictimization experience. Therefore, using 432 cases of cyberbullying victimization (i.e., victims-only as passive victims and victim-bullies as aggressive victims) in a sample of Hong Kong school-age Chinese adolescents, this study examines the effects of different demographics (i.e., age and sex) and psychosocial characteristics (i.e., self-esteem, empathy, prosocial behavior, family attachment, perception of a harmonious school, sense of school belonging and commitment, and positive school experience and involvement) on different victim coping approaches (i.e., avoidant, aggressive, passive, and active). Findings indicate that older male adolescents who engage in prosocial behavior are likely to employ an active approach, while those who reported fewer positive school experiences and involvement are likely to use an avoidant coping style in coping with their victimization. Adolescents who perceived their school as a harmonious place but with fewer positive school experiences and involvement are likely to adopt a passive coping style, while those who retaliated against their bullying perpetrators are likely to be males and high in empathy level. Implications are offered to inform practices in aiding adolescents to cope with potential cyberbullying victimization effectively.